2021
DOI: 10.1159/000517518
|View full text |Cite
|
Sign up to set email alerts
|

When Anxiety and Depression Coexist: The Role of Differential Diagnosis Using Clinimetric Criteria

Abstract: Depressive and anxiety disorders are frequently associated. Depression may be a complication of anxiety and anxiety can complicate depression. The nature of their relationship has been a source of controversy. Reviews generally base their conclusions on randomized controlled trials and meta-analyses that refer to the average patient and often clash with the variety of clinical presentations that may occur when anxiety and depression coexist. The aim of this review was to examine the literature according to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 64 publications
0
30
0
2
Order By: Relevance
“…Thus, in my opinion, out of three articles dealing with a similar topic, only one seems to be useful to clinicians [2]. Two of these articles [2, 3] would probably not fulfill usual journals’ criteria for a review article (see below), and one is not really clinically useful [1]. The utility of another one [3] is also doubtful.…”
Section: Are All Review Articles Useful and Have Clear Goals?mentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, in my opinion, out of three articles dealing with a similar topic, only one seems to be useful to clinicians [2]. Two of these articles [2, 3] would probably not fulfill usual journals’ criteria for a review article (see below), and one is not really clinically useful [1]. The utility of another one [3] is also doubtful.…”
Section: Are All Review Articles Useful and Have Clear Goals?mentioning
confidence: 99%
“…Three recent articles [1][2][3] on the seemingly very similar topic of coexistence of anxiety and depression are a case in point of the lack of clarity of what a review article is and what its attributes and goals are The first one by Saha et al [1] is a systematic review and meta-analysis which "found robust and consistent evidence of comorbidity between broadly defined mood and anxiety disorders. Clinicians should be vigilant for the prompt identi-fication and treatment of this common type of comorbidity."…”
Section: Are All Review Articles Useful and Have Clear Goals?mentioning
confidence: 99%
See 3 more Smart Citations